Quad‐Band Transmissive Metasurface with Linear to Dual‐Circular Polarization Conversion Simultaneously. Issue 8 (8th July 2021) - Li, Zhuo Yue; Li, Si Jia; Han, Bo Wen; Huang, Guo Shuai; Guo, Ze Xu; Cao, Xiang Yu
Abstract: Metasurface is a momentous periodic or aperiodic microstructure which has capabilities in controlling polarization of electromagnetic waves. To realize polarization controlling, many microstructures have been designed to achieve the function. However, multi‐band linear to dual‐circular polarization converter is rarely proposed and designed in the last few years. Here, a quad‐band dual‐circular transmissive metasurface (QCT‐MS) is proposed to manipulate polarization of transmissive wave. QCT‐MS is designed as a three‐layer microstructure, with substrate in the middle and two metal patches in the shape of bi‐symmetrical arrow on both sides. The proposed microstructure manipulates linear polarization waves to dual‐circular polarization waves in different frequency bands with x ‐polarized or y ‐polarized incident waves. The experimental and simulated results reveal that left‐hand circularly polarized waves can be realized in 3.14–3.32,  4.41–4.46,  and 14.82–16.05 GHz while the right‐hand circularly polarized waves can be achieved from 9.45 to 10.12 GHz for QCT‐MS with x ‐polarized incidences. Moreover, the simulated results also demonstrate its characteristics of wide‐angle transmission and periodic changes. The proposed transmissive metasurface can be utilized in multiband communication and multifunctional dual‐circularly polarized antenna systems. Abstract : A quad‐band dual‐circular transmissive metasurface is proposed to manipulate polarization of transmissive wave. The metasurface converts linear polarization wave to dual‐circular polarization wave in different frequency bands with different polarized incidences and has application in multiband communication and multifunctional dual‐circularly polarized antenna systems.